Paired involvement of human-specific Olduvai domains and NOTCH2NL genes in human brain evolution - Fiddes, Ian T.; Pollen, Alex A.; Davis, Jonathan M.; Sikela, James M. (Human genetics, 2019)
Sequences encoding Olduvai (DUF1220) protein domains show the largest human-specific increase in copy number of any coding region in the genome and have been linked to human brain evolution. Most human-specific copies of Olduvai (119/165) are encoded by three NBPF genes that are adjacent to three human-specific NOTCH2NL genes that have been shown to promote cortical neurogenesis. Here, employing genomic, phylogenetic, and transcriptomic evidence, we show that these NOTCH2NL / NBPF gene pairs evolved jointly, as two-gene units, very recently in human evolution, and are likely co-regulated. Remarkably, while three NOTCH2NL paralogs were added, adjacent Olduvai sequences hyper-amplified, adding 119 human-specific copies. The data suggest that human-specific Olduvai domains and adjacent NOTCH2NL genes may function in a coordinated, complementary fashion to promote neurogenesis and human brain expansion in a dosage-related manner.